Analisis Pengukuran Usability Aplikasi DAPODIK Kabupaten Karawang Dengan Metode Use Questionnaire dan IPA - Lubis, Baginda Oloan; Gunawan, Wahyu; Hendri, Hendri; Oscar, Dony; Salim, Agus (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2024)
Choosing an internet-based application as a communication tool is considered a smart decision due to its ability to deliver information or messages to users anywhere without being limited by region or location. An application created by an institution can provide important information about the institution's activities to users, while users can access detailed data through the application. Currently, the Dapodik application has been implemented in various schools in Kabupaten Karawang. However, the use of this application faces several problems, including frequent system errors that cause double transactions and require a long time to update data. Based on these problems, this study was conducted to determine the extent of the advantages and disadvantages of the Dapodik application. The research was conducted using the Use Questionnaire and Importance Performance Analysis methods using a questionnaire distributed to 50 application users using google form. The results of this study obtained with the Importance Performance Analysis method produce a priority map for improving the Dapodik application. The map is divided into quadrant I as the top priority from the user's perspective. In quadrant II, there are aspects of the Dapodik application which are areas of achievement or excellence that must be maintained because they have met user expectations, namely the appearance of the Dapodik application is easy to recognize, the Dapodik application is easy to operate and the color combination of the Dapodik application is pleasing to the eye and not boring.